Initial investigation on the feasibility of porcine red blood cells from genetically modified pigs as an alternative to human red blood cells for transfusion - Park, Sangkeun; Lee, Haneulnari; Park, Eun Mi; Roh, Juhye; Kang, Pul Ip; Shim, Joohyun; Choi, Kimyung; Kang, Hee Jung (Frontiers in Immunology, 2023)
The decline in blood donation rates and the ongoing shortage of blood products pose significant challenges to medical societies. One potential solution is to use porcine red blood cells (pRBCs) from genetically modified pigs as an alternative to human red blood cells (hRBCs). However, adverse immunological reactions remain a significant obstacle to their use. This study aimed to evaluate the compatibility of diverse genetically modified pRBCs with human serum.We acquired human complement-competent serum, complement 7 (C7)-deficient serum, and hRBCs from all ABO blood types. Additionally, we used leftover clinical samples from health checkups for further evaluation. pRBCs were collected from wild-type (WT) and genetically modified pigs: triple knockout (TKO), quadruple KO (QKO), and TKO/hCD55.hCD39 knockin (hCD55.hCD39KI). The extent of C3 deposition on RBCs was measured using flow cytometry after incubation in C7-deficient serum diluted in Ca ++ -enriched or Ca ++ -depleted and Mg ++ -enriched buffers. The binding of immunoglobulin (Ig) M/IgG antibody to RBCs after incubation in ABO-type human serum was evaluated using flow cytometry. Naïve human serum-or sensitized monkey serum-mediated hemolysis was also evaluated. Phagocytosis was assessed by incubating labeled RBCs with the human monocytic cell line THP-1 and measurement by flow cytometry.All three genetic modifications significantly improved the compatibility of pRBCs with human serum relative to that of WT pRBCs. The extent of IgM/IgG binding to genetically modified pRBCs was lower than that of WT pRBCs and similar to that of O-type hRBCs. Total and alternative pathway complement activation in all three genetically modified pRBCs was significantly weaker than that in WT pRBCs and did not differ from that in O-type hRBCs. The extent of serum-mediated hemolysis and phagocytosis of these genetically modified pRBCs was low and similar to that of O-type hRBCs. Sensitized monkey serum-mediated hemolysis in QKO and TKO/hCD55.hCD39KI pRBCs was higher than in O-type hRBCs but lower than in TKO pRBCs.The elimination of porcine carbohydrate antigens in genetically modified pigs significantly enhanced pRBC compatibility with naïve human sera, which was comparable to that of O-type hRBCs. These findings provide valuable insights into the development of pRBCs as potential alternatives to hRBCs.